Prejuicios del tratamiento de lo psíquico. Una visión fenomenológica - Trilles Calvo, Karina P. (Logos. Anales del Seminario de Metafísica, 2005)
The fundamental objective of this paper is to show the prejudices that underlie the treatment of the mental illness. We begin defining how our life is in the “natural attitude” in which we accept as natural certain beliefs without foundation. We defend that the epojé is the appropriate method to make that commitent presents. After setting the method, we describe what happens to a mental sick person in a psychiatrist- psychologist’s cabinet and, from this situation, we begin to figure out the prejudices of “double realities”, “naturalistic”, “identical method” and the “naturalization of the psychic symptom”.
Keywords: Phenomenology - Prejudice - mental Illness